A calcium carbonate filling masterbatch and its preparation method and application
Through ultrasonic atomization and electrostatic reaction modified calcium carbonate, combined with solid-phase shear milling technology, a modified resin load-modified calcium carbonate is formed, which solves the problem of poor aging resistance of polypropylene fiber non-woven fabrics and realizes carbonic acid The good dispersion and anti-aging properties of calcium-filled masterbatches in non-woven fabrics extend the service life of PP non-woven fabrics.
Patent Information
- Application Number
- CN202211181040.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-09-27
AI Technical Summary
Polypropylene fiber non-woven fabrics are prone to aging and degradation during processing, resulting in insufficient dispersion of anti-aging agents, affecting product performance and service life.
The preparation method of calcium carbonate filled masterbatch is adopted to modify calcium carbonate through ultrasonic atomization and electrostatic reaction, combined with solid-phase shear milling technology, to improve the dispersion and synergistic compatibility of the anti-aging agent to form load-modified carbonic acid Modified resin of calcium and mixed with dispersant and lubricant to extrude and granulate.
The good dispersion and anti-aging properties of calcium carbonate-filled masterbatches in non-woven fabrics are achieved, and the service life of PP non-woven fabrics is extended.
Smart Images

Figure CN115505147B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a calcium carbonate filling masterbatch and a preparation method and application thereof. Background Art
[0002] Non-woven fabrics are moisture-proof, breathable, easy to decompose, non-toxic and non-irritating, low-priced and recyclable. They have been widely used in the fields of medical treatment, clothing and environmental protection, especially in high-tech penetration and new materials. With the continuous development of non-woven fabric technology and the expansion of application fields, higher requirements have been put forward for non-woven fabrics. The raw material polypropylene fiber (PP) for producing non-woven fabrics has gradually shown its own defects. Although PP is light, strong, elastic, wear-resistant, corrosion-resistant, and has electrical insulation and warmth retention, it also has the disadvantages of poor heat resistance and aging resistance. Due to the influence of processing temperature and PP's own structure during processing, as well as light and oxidation during use, PP non-woven fabrics are prone to aging and degradation, resulting in a sharp decline in the physical and chemical properties of non-woven fabrics, reducing the service life of the product. Therefore, modifying PP to develop new varieties has become the main direction of PP development.
[0003] Domestic and foreign scholars have done a lot of research on improving the anti-aging properties of polypropylene fibers, mainly by adding anti-aging agents to improve the anti-aging properties of polypropylene fibers. However, the modification method of directly adding anti-aging agents has a fatal disadvantage, that is, the anti-aging agent cannot achieve a good dispersion effect in the product. Especially in the non-woven fabric industry, non-woven fabrics prepared by directly mixing anti-aging agents with polypropylene fibers often have a series of quality problems, such as easy to cause non-woven fabrics to break during the production process, reduce production efficiency, and cause the anti-aging agent to fail to play its due role. Therefore, in the anti-aging of PP non-woven fabrics, it is very important to solve the dispersion problem of anti-aging agents. At present, the main method is to add anti-aging masterbatch during production to improve the dispersibility of anti-aging agents. However, the anti-aging agents in the existing anti-aging masterbatch are not fully dispersed due to the process or the product itself not meeting the standards, and still cannot achieve the ideal dispersion effect. Summary of the invention
[0004] The object of the present invention is to provide a calcium carbonate filling masterbatch and a preparation method and application thereof. The calcium carbonate filling masterbatch provided by the present invention has good dispersibility and excellent anti-aging performance.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a calcium carbonate filler masterbatch, comprising the following steps:
[0007] (1) ultrasonically atomizing the anti-aging agent aqueous solution, and the obtained atomized droplets react electrostatically with the dusty calcium carbonate powder to obtain modified calcium carbonate;
[0008] (2) mixing the resin and the antioxidant and then performing solid phase shear milling to obtain a modified resin;
[0009] (3) mixing the modified calcium carbonate and the modified resin and performing solid phase shear milling to obtain a modified resin loaded with modified calcium carbonate;
[0010] (4) mixing the modified resin loaded with modified calcium carbonate, a dispersant and a lubricant, and then extruding and granulating the mixture to obtain a calcium carbonate filling masterbatch;
[0011] The antioxidant in the antioxidant aqueous solution of step (1) and the antioxidant in step (2) include a low-basic hindered amine antioxidant and a reactive hindered amine antioxidant; the low-basic hindered amine antioxidant has a pH of Kb 3 to 5;
[0012] There is no time sequence restriction between step (1) and step (2).
[0013] Preferably, the mass ratio of the antioxidant in the antioxidant aqueous solution of step (1) to the low-basic hindered amine antioxidant and the reactive hindered amine antioxidant in the antioxidant of step (2) is 1:0.5-1.5.
[0014] Preferably, the mass ratio of the antioxidant to the calcium carbonate powder in the antioxidant aqueous solution in step (1) is 0.05-0.25:100.
[0015] Preferably, the mass ratio of the anti-aging agent to the resin in step (2) is 0.05-0.25:100.
[0016] Preferably, the low-alkalinity hindered amine antioxidant includes one or both of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate and BASF hindered amine light stabilizer CHIMASSORB 119FL; the reactive hindered amine antioxidant includes one or both of CYASORB UV-3529 and light stabilizer 3346.
[0017] Preferably, the mass ratio of the modified calcium carbonate to the modified resin is 50-80:20-50; the mass ratio of the modified calcium carbonate to the dispersant is 50-80:2-5; the mass ratio of the modified calcium carbonate to the lubricant is 50-80:0.2-0.5.
[0018] Preferably, the particle size of the modified resin is 0.65 to 0.85 mm.
[0019] Preferably, the resin is one or more of polypropylene resin, high-density polyethylene resin and polylactic acid, with a particle size of 0.65 to 0.85 mm and a melt index of 25 to 35 g / 10 min; the content of calcium carbonate powder with a particle size of 2 microns in the calcium carbonate powder is 25wt% to 35wt%.
[0020] The present invention also provides a calcium carbonate filling masterbatch obtained by the preparation method described in the above scheme, wherein the particle size is 2 to 5 mm.
[0021] The present invention also provides the use of the calcium carbonate filling masterbatch described in the above scheme in non-woven fabrics.
[0022] The invention provides a preparation method of calcium carbonate filled masterbatch, the invention adopts multiple pre-dispersion processes to prepare the masterbatch, and the anti-aging agent is dispersed three times: first, the two raw materials, resin and calcium carbonate, are modified by the anti-aging agent respectively, and the anti-aging agent is modified by atomization and electrostatic adsorption, and the dispersion of the modified anti-aging agent is more uniform compared with the commonly used stirring and blending; second, the resin and the anti-aging agent are fully dispersed by solid phase shearing and grinding; third, the modified resin and the modified calcium carbonate are mixed uniformly by solid phase shearing and grinding again, and the dispersion effect is better than the commonly used mechanical stirring and blending, which solves the dispersion problem of the anti-aging agent and enables the anti-aging agent to fully play its role. The invention is compounded with a low-alkalinity hindered amine anti-aging agent and a reactive hindered amine anti-aging agent. Compared with traditional hindered amines, the reactive hindered amine anti-aging agent has a reactive group in its structure, which can be bonded to the modified resin in the masterbatch preparation process, and can also be bonded to the non-woven fabric polymer in the non-woven fabric processing process, so as to obtain permanent anti-aging property, and at the same time improve the synergistic compatibility stability between the anti-aging agent and the resin. The present invention uses solid phase shear grinding technology without surface treatment, can effectively improve the interface compatibility between calcium carbonate and resin, and achieves a good pre-dispersion effect.
[0023] In addition, the present invention uses an ultrasonic atomization method to perform anti-aging modification on calcium carbonate, which saves energy and reduces consumption while also improving the modification effect compared to the traditional commonly used heating atomization method.
[0024] Furthermore, the present invention can grind calcium carbonate and resin together through solid phase shear grinding technology, produce obvious grinding aid effect, increase the addition amount of calcium carbonate, and then prepare high-filling masterbatch.
[0025] The present invention also provides a calcium carbonate filler masterbatch obtained by the preparation method described in the above scheme, with a particle size of 2 to 5 mm. The calcium carbonate filler masterbatch provided by the present invention has good dispersibility in non-woven fabrics, excellent anti-aging performance, and good stability.
[0026] The present invention also provides the application of the calcium carbonate filling masterbatch in the above scheme in non-woven fabrics. The calcium carbonate filling masterbatch provided by the present invention can be well dispersed when added to non-woven fabrics, and is particularly suitable for PP non-woven fabrics, which can solve the problem of poor aging resistance of existing PP non-woven fabrics and extend the service life of PP non-woven fabrics. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 This is a physical picture of the calcium carbonate filling masterbatch prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a calcium carbonate filler masterbatch, comprising the following steps:
[0030] (1) ultrasonically atomizing the anti-aging agent aqueous solution, and the obtained atomized droplets react electrostatically with the dusty calcium carbonate powder to obtain modified calcium carbonate;
[0031] (2) mixing the resin and the antioxidant and then performing solid phase shear milling to obtain a modified resin;
[0032] (3) mixing the modified calcium carbonate and the modified resin and performing solid phase shear milling to obtain a modified resin loaded with modified calcium carbonate;
[0033] (4) mixing the modified resin loaded with modified calcium carbonate, a dispersant and a lubricant, and then extruding and granulating the mixture to obtain a calcium carbonate filling masterbatch;
[0034] The antioxidant in the antioxidant aqueous solution of step (1) and the antioxidant in step (2) include a low-basic hindered amine antioxidant and a reactive hindered amine antioxidant; the low-basic hindered amine antioxidant has a pH of Kb 3 to 5;
[0035] There is no time sequence restriction between step (1) and step (2).
[0036] The present invention ultrasonically atomizes an anti-aging agent aqueous solution, and the obtained atomized droplets react electrostatically with the dusty calcium carbonate powder to obtain modified calcium carbonate. In the present invention, the content of calcium carbonate powder with a particle size of 2 microns in the calcium carbonate powder is preferably 25wt% to 35wt%, more preferably 27wt% to 32wt%, and further preferably 28wt% to 31wt%; the preparation method of the calcium carbonate powder comprises the following steps: washing, coarsely crushing and grinding the calcite ore in sequence to obtain calcium carbonate powder; the purity of the calcite ore is not less than 97%, more preferably not less than 98%; the grinding is preferably wet grinding; the anti-aging agent in the aqueous solution The aging agent includes a low-basic hindered amine antioxidant and a reactive hindered amine antioxidant; the mass ratio of the low-basic hindered amine antioxidant and the reactive hindered amine antioxidant in the antioxidant aqueous solution is preferably 1:0.5-1.5, more preferably 1:0.8-1.2; the low-basic hindered amine antioxidant preferably includes one or two of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate and BASF hindered amine light stabilizer CHIMASSORB 119FL; the reactive hindered amine antioxidant preferably includes one or two of CYASORBUV-3529 and light stabilizer 3346; the P of the low-basic hindered amine antioxidant is preferably 1:0.5-1.5, more preferably 1:0.8-1.2. Kb is 3 to 5, preferably 4; the mass concentration of the anti-aging agent aqueous solution is preferably 30% to 40%, more preferably 34% to 37%; the mass ratio of the anti-aging agent to the calcium carbonate powder in the anti-aging agent aqueous solution is preferably 0.05 to 0.25:100, more preferably 0.10 to 0.20:100, and further preferably 0.15 to 0.20:100.
[0037] In the present invention, the frequency of the ultrasonic atomization is preferably 2-3 MHz, more preferably 2.4 MHz, and the time of the ultrasonic atomization is preferably 20-35 minutes, more preferably 30 minutes; the ultrasonic atomization equipment is preferably an ultrasonic atomizer with electronic high-frequency oscillation, and the anti-aging agent aqueous solution generates water mist through the atomizer, and releases a large amount of negative ions during the atomization process; in a specific embodiment of the present invention, the anti-aging agent water mist carrying negative ions is sent into the modified cabin through the induced draft fan, and generates an electrostatic reaction with the calcium carbonate dust sent into the modified cabin through another induced draft fan; the electrostatic reaction The corresponding temperature is preferably room temperature, and the reaction time is preferably 10 to 20 minutes, more preferably 13 to 15 minutes; after the electrostatic reaction is completed, the obtained reaction product is preferably precipitated, dried, depolymerized and dispersed in sequence; the present invention has no special requirements for the precipitation, and the obtained reaction product can be precipitated; the drying temperature is preferably 95 to 105°C, more preferably 101 to 105°C, and the insulation time is preferably 10 to 15 minutes, more preferably 11 to 13 minutes; the present invention has no special requirements for the depolymerization and dispersion, and the depolymerization and dispersion operations commonly used in the art can be used.
[0038] The invention mixes the resin and the anti-aging agent and then performs solid phase shearing milling to obtain the modified resin. In the present invention, the resin is preferably one or more of polypropylene resin, high-density polyethylene resin and polylactic acid, the particle size of the resin is preferably 0.65-0.85 mm, more preferably 0.70-0.80 mm, the melt index of the resin is preferably 25-35 g / 10 min, more preferably 28-32 g / 10 min; the anti-aging agent preferably includes a low-alkalization hindered amine anti-aging agent and a reactive hindered amine anti-aging agent; the types and proportions of the low-alkalization hindered amine anti-aging agent and the reactive hindered amine anti-aging agent are consistent with the above scheme, and are not repeated here; the mass ratio of the anti-aging agent to the resin is preferably 0.05-0.25:100, more preferably 0.15-0.25:100; the present invention has no special requirements for the parameters of the solid phase shear milling, and the anti-aging agent and the resin are mixed evenly and milled into a modified resin powder of the target particle size; the equipment for the solid phase shear milling is preferably a grinding disc-shaped mechanochemical reactor. The present invention pre-disperses the resin and the anti-aging agent through solid phase shear milling, mixes the anti-aging agent and the resin evenly, and grinds them into modified resin powder with target particle size.
[0039] After obtaining modified calcium carbonate and modified resin, the present invention mixes the modified calcium carbonate and modified resin and then performs solid phase shear milling to obtain modified resin loaded with modified calcium carbonate. In the present invention, the content of calcium carbonate powder with a particle size of 2 microns in the calcium carbonate powder is preferably 25wt% to 35wt%, more preferably 28wt% to 31wt%; the particle size of the modified resin is preferably 65 to 85 microns, more preferably 70 to 80 microns; the mass ratio of the modified calcium carbonate and the modified resin is preferably 50 to 80:20 to 50, more preferably 60 to 70:30 to 40; the equipment for solid phase shear milling is preferably a grinding disc-shaped force chemical reactor, and the modified calcium carbonate and the modified resin are uniformly mixed by solid phase shear milling without surface treatment, which can effectively improve the interface compatibility between the modified calcium carbonate and the modified resin; the particle size of the modified resin loaded with modified calcium carbonate is preferably 65 to 85 microns, more preferably 74 to 82 microns.
[0040] After obtaining the modified resin loaded with modified calcium carbonate, the present invention mixes the modified resin loaded with modified calcium carbonate, a dispersant and a lubricant, and then extrudes and granulates them to obtain a calcium carbonate filling masterbatch. In the present invention, the dispersant preferably includes one or more of high melting point PP wax (melting point 120-150°C), OPE wax and vinyl bisstearamide; the lubricant preferably includes one or more of TAS-2A lubricant, super lubricant SFR-1 and SFR-2; the mass ratio of the modified calcium carbonate and the dispersant is preferably 50-80:2-5, more preferably 60-70:3-5; the mass ratio of the modified calcium carbonate and the lubricant is preferably 50-80:0.2-0.5, more preferably 60-70:0.4-0.5; the mixing equipment is preferably a high mixer; the mixing speed is preferably 900-1200rpm, more preferably 1000rpm, and the mixing time is preferably 15-25 minutes, more preferably 20 minutes.
[0041] In the present invention, the extrusion granulation equipment is preferably a twin-screw extruder; the screw aspect ratio of the twin-screw extruder is preferably 30-40:1, more preferably 32-37:1; the rotation speed of the twin-screw extruder is preferably 40-55 Hz, more preferably 45-50 Hz; the extrusion granulation is preferably adding the mixed material obtained by mixing into a twin-screw extruder; the twin-screw extruder is preferably divided into nine working sections, namely zone one, zone two, zone three, zone four, zone five, zone six, zone seven, zone eight and zone nine; the temperature of zone one is preferably 160-165°C, more preferably 162-165°C; the temperature of zone two is preferably 163-170°C, more preferably 165-170°C; the temperature of zone three is preferably 165- 175 ℃, more preferably 169-175 ℃; the temperature of the fourth zone is preferably 165-175 ℃, more preferably 169-173 ℃; the temperature of the fifth zone is preferably 168-180 ℃, more preferably 175-180 ℃; the temperature of the sixth zone is preferably 173-185 ℃, more preferably 178-183 ℃; the temperature of the seventh zone is preferably 178-188 ℃, more preferably 179-185 ℃; the temperature of the eighth zone is preferably 182-190 ℃, more preferably 185-190 ℃; the temperature of the ninth zone is preferably 185-195 ℃, more preferably 188-192 ℃; the temperature of the die head in the twin-screw extruder is preferably 190-200 ℃, more preferably 195-200 ℃.
[0042] In the present invention, after the extrusion is completed, the extruded strips are preferably cooled, dried and pelletized in sequence; the cooling is preferably carried out by circulating tap water cooling; the drying is preferably carried out by hot air drying; the temperature of the hot air drying is preferably 70 to 90°C, more preferably 80°C, and the insulation time is preferably 8 to 13 minutes, more preferably 10 minutes; the particle size of the particles obtained by pelletizing is preferably 2 to 5 mm, more preferably 3 to 4 mm.
[0043] The present invention also provides a calcium carbonate filling masterbatch obtained by the preparation method described in the above scheme, wherein the particle size is 2 to 5 mm.
[0044] In the present invention, the particle size of the calcium carbonate filler masterbatch is 2 to 5 mm, preferably 3 to 5 mm, and more preferably 3 to 4 mm.
[0045] The present invention also provides the use of the calcium carbonate filling masterbatch described in the above scheme in non-woven fabrics.
[0046] In the present invention, the non-woven fabric preferably includes PP non-woven fabric, high-density polyethylene non-woven fabric or polylactic acid non-woven fabric; the application preferably includes the following steps: heating and mixing the calcium carbonate filling masterbatch and the matrix resin to obtain a melt, and then sequentially performing spunbonding, web laying, spunlacing and needle punching and hot rolling reinforcement on the obtained melt to obtain a non-woven fabric. In the present invention, the mass ratio of the calcium carbonate filling masterbatch and the matrix resin is preferably 1-2:4-5, more preferably 1-1.8:4.5-5; the matrix resin in the non-woven fabric is preferably the same type as the modified resin in the calcium carbonate filling masterbatch; the matrix resin preferably includes one or more of PP, high-density polyethylene non-woven fabric and polylactic acid.
[0047] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0048] Example 1
[0049] The raw ore with a calcium carbonate content of ≥97% is roughly crushed into a 325-mesh coarse powder, and then wet-ground into a 2500-mesh powder. The antioxidant is bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate and CYASORB UV-3529 in a mass ratio of 1:1. The antioxidant accounting for 0.1% of the mass of calcium carbonate is prepared into an antioxidant solution with a mass solubility of 35%. The antioxidant solution is used to atomize and modify the 2500-mesh calcium carbonate, and the atomized precipitated calcium carbonate is dried, depolymerized, and dispersed.
[0050] A polypropylene resin with a melt index of 30 g / 10 min and an anti-aging agent of 0.1% by weight of the resin are ground to 2500 meshes by a grinding disc force chemical reactor, and then the obtained modified calcium carbonate and the obtained modified resin are mixed in a mass ratio of 3:2, and ground to 3000 meshes by a grinding disc force chemical reactor to form a modified resin loaded with modified calcium carbonate;
[0051] The obtained modified resin loaded with modified calcium carbonate was uniformly blended with PP wax with a melting point of 130°C in a mass ratio of 100:3 and TAS-2A lubricant in a mass ratio of 1000:3 by a high-speed mixer, and finally added into a twin-screw extruder for extrusion granulation at 170-200°C, with the temperatures of zone 163°C, zone 2 165°C, zone 3 170°C, zone 4 173°C, zone 5 175°C, zone 6 178°C, zone 7 180°C, zone 8 185°C, zone 9 190°C and die head 195°C to obtain calcium carbonate filled masterbatch. Figure 1 This is a physical picture of the calcium carbonate filling masterbatch prepared in Example 1 of the present invention. The calcium carbonate filling masterbatch provided by the present invention has uniform components, transparent texture and moderate particle size.
[0052] The prepared calcium carbonate filling masterbatch was added to a polypropylene resin having a matching melt index of 30 g / 10 min. The mass ratio of the calcium carbonate filling masterbatch to the polypropylene resin was 1:5. A PP non-woven fabric was prepared and related properties were tested.
[0053] Example 2
[0054] The raw ore with a calcium carbonate content of ≥97% is roughly crushed into a coarse powder of 325 mesh, and then wet-ground into a powder of 2500 mesh. The anti-aging agent is a BASF hindered amine light stabilizer CHIMASSORB 119FL and a light stabilizer 3346 (containing a triazine hindered amine condensate) in a mass ratio of 1:1. The anti-aging agent accounting for 0.1% of the mass of the calcium carbonate is prepared into an anti-aging agent solution with a mass solubility of 35%. The anti-aging agent solution is used to atomize and modify the 2500-mesh calcium carbonate, and the atomized precipitated calcium carbonate is dried, depolymerized, and dispersed;
[0055] A polypropylene resin having a melt index of 28 g / 10 min and an anti-aging agent containing 0.1% of the resin mass are ground to 2500 meshes by a grinding disc force chemical reactor to obtain a modified resin, and then the obtained modified calcium carbonate is mixed with the obtained modified resin in a mass ratio of 1:1, and ground to 3000 meshes by a grinding disc force chemical reactor to obtain a modified resin loaded with modified calcium carbonate;
[0056] The obtained modified resin loaded with modified calcium carbonate was uniformly blended with vinyl bisstearamide at a mass ratio of 100:4 and TAS-2A lubricant at a mass ratio of 1000:2 by a high-speed mixer, and finally added into a twin-screw extruder for extrusion granulation at 170-200°C, with the temperatures of zone 163°C, zone 2 165°C, zone 3 170°C, zone 4 173°C, zone 5 175°C, zone 6 178°C, zone 7 180°C, zone 8 185°C, zone 9 193°C and die head 198°C to obtain calcium carbonate filled masterbatch.
[0057] The prepared calcium carbonate filling masterbatch was added to a polypropylene resin having a matching melt index of 30 g / 10 min. The mass ratio of the calcium carbonate filling masterbatch to the polypropylene resin was 1:5. A PP non-woven fabric was prepared and related properties were tested.
[0058] Comparative Example 1
[0059] The raw ore with calcium carbonate content ≥97% is roughly crushed into 325 mesh coarse powder, and then wet-ground into 2500 mesh powder. The polypropylene resin with a melt index of 30g / 10min is ground to 2500 mesh by a grinding disc mechanochemical reactor;
[0060] The obtained calcium carbonate powder was mixed with a 2500 mesh resin in a mass ratio of 1:1, and ground to 3000 mesh by a grinding disc force chemical reactor. The obtained calcium carbonate-loaded resin was then mixed with an anti-aging agent in a mass ratio of 1000:1, with vinyl bisstearamide in a mass ratio of 100:4, and with TAS-2A lubricant in a mass ratio of 1000:2 by a high-speed mixer. The anti-aging agent was BASF hindered amine light stabilizer CHIMASSORB 119FL and light stabilizer 3346 (containing triazine hindered amine condensate) are matched in a mass ratio of 1:1, mixed evenly and added into a twin-screw extruder for extrusion granulation at 170-200°C, with the temperatures of zone 163°C, zone 2 165°C, zone 3 170°C, zone 4 173°C, zone 5 175°C, zone 6 178°C, zone 7 180°C, zone 8 185°C, zone 9 192°C and die head 197°C to obtain calcium carbonate filled masterbatch.
[0061] The prepared calcium carbonate filling masterbatch was added to a polypropylene resin having a matching melt index of 30 g / 10 min. The mass ratio of the calcium carbonate filling masterbatch to the polypropylene resin was 1:5. A PP non-woven fabric was prepared and related properties were tested.
[0062] The relevant performance test reference standards of the calcium carbonate filled masterbatch prepared in Examples 1 to 2 and Comparative Example 1 after aging are as follows: the breaking strength and breaking elongation are tested according to GB / T24218.3-2010, the xenon lamp aging test is tested according to GB / T32088-2015, and the tear strength is tested according to GB / T 455-2002. The test results are shown in Table 1.
[0063] Table 1 Performance test results of calcium carbonate filling masterbatch prepared in Examples 1 to 2 and Comparative Example 1
[0064]
[0065]
[0066] From the performance data of Examples 1 to 2 and Comparative Example 1 in Table 1, it can be seen that after xenon lamp aging, the breaking strength, tear strength and elongation at break of Examples 1 and 2 are significantly reduced compared with Comparative Example 1. It can be seen that the preparation method provided by the present invention can significantly improve the aging resistance of the non-woven fabric, which indirectly proves that the calcium carbonate filler masterbatch is well dispersed in the non-woven fabric.
[0067] It can be seen from the above embodiments that the calcium carbonate filler masterbatch provided by the present invention has good dispersibility in non-woven fabrics and excellent anti-aging performance, and is particularly suitable for PP non-woven fabrics. It can solve the problem of poor aging resistance of existing PP non-woven fabrics and extend the service life of PP non-woven fabrics.
[0068] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a calcium carbonate filler masterbatch, characterized in that: The following steps are involved: (1) ultrasonically atomizing the anti-aging agent aqueous solution, and the obtained atomized droplets react electrostatically with the dusty calcium carbonate powder to obtain modified calcium carbonate; (2) mixing the resin and the antioxidant and then performing solid phase shear milling to obtain a modified resin; (3) mixing the modified calcium carbonate and the modified resin and subjecting them to solid phase shear milling to obtain a modified resin loaded with modified calcium carbonate; (4) mixing the modified resin loaded with modified calcium carbonate, a dispersant and a lubricant, and then extruding and granulating the mixture to obtain a calcium carbonate filling masterbatch; The antioxidant in the antioxidant aqueous solution of step (1) and the antioxidant in step (2) include a low-basic hindered amine antioxidant and a reactive hindered amine antioxidant; the low-basic hindered amine antioxidant has a pH of Kb is 3 to 5; the mass ratio of the antioxidant in the antioxidant aqueous solution of step (1) to the low-basic hindered amine antioxidant and the reactive hindered amine antioxidant in the antioxidant of step (2) is 1:0.5 to 1.5; There is no time sequence limit between step (1) and step (2); The mass ratio of the antioxidant to the calcium carbonate powder in the antioxidant aqueous solution of step (1) is 0.05-0.25:100; The mass ratio of the anti-aging agent to the resin in step (2) is 0.05-0.25:100; The mass ratio of the modified calcium carbonate to the modified resin is 50-80:20-50; the mass ratio of the modified calcium carbonate to the dispersant is 50-80:2-5; the mass ratio of the modified calcium carbonate to the lubricant is 50-80:0.2-0.
5.
2. The preparation method according to claim 1, characterized in that: The low-alkalinity hindered amine antioxidant includes one or both of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate and BASF hindered amine light stabilizer CHIMASSORB119FL; the reactive hindered amine antioxidant includes one or both of CYASORB UV-3529 and light stabilizer 3346.
3. The preparation method according to claim 1, characterized in that: The particle size of the modified resin is 0.65-0.85 microns.
4. The preparation method according to claim 1, characterized in that: The resin is one or more of polypropylene resin, high-density polyethylene resin and polylactic acid, with a particle size of 0.65-0.85 mm and a melt index of 25-35 g / 10 min; the content of calcium carbonate powder with a particle size of 2 microns in the calcium carbonate powder is 25wt%-35wt%.
5. The calcium carbonate filling masterbatch obtained by the preparation method according to any one of claims 1 to 4 has a particle size of 2 to 5 mm.
6. Use of the calcium carbonate filling masterbatch according to claim 5 in non-woven fabrics.
Citation Information
Patent Citations
Highly-filled calcium carbonate masterbatch for non-woven fabrics and preparation method thereof
CN101914239A
Filling material master batch used for non-woven fabrics and preparing process thereof
CN104177696A